Contribución al conocimiento limnológico del Río Bermejo en su tramo inferior - Bonetto, Argentino A.; Zalocar, Yolanda; Pedrozo, Fernando L.; Bonetto, Carlos (Ecosur, 2024)
The main limnological features of the Bermejo river have been recorded at Puerto Velaz, 30 kilometers upstream the river mouth. The most stricking feature of the Bermejo river is an extremely high rate of suspended solid. The low water transparency limited the phytoplankton growth. Therefore phytoplankton density and primary production were undetectable during the flood period, reaching a máximum of 170 ind/ml and 30 mgC/m2/d respectively during the low water period. Diatoms (Melosira) and Chlorophytes (Scenedesmus) were dominant. The suspended solid concentration reached a máximum of 9,500 mg/1 in the summer flood, during the studied period. The dissolved oxygen was always near saturation. Chemical oxygen demand and water transparency were very low. Conductivity ranged from 850 uS/cm to 310 /uS/cm.